Enolates of 2-Isothiocyanatocarboxylic Esters: Synthesis of Thiazolo[5,4-d]-thiazole Derivatives and 2-Thioxo-1,3-thiazolidine-4-carboxylates - Cież, Dariusz; Kalinowska-Tłuścik, Justyna (Synthesis, 2012)
An oxidative dimerization of titanium(IV) enolates derived from menthyl esters of 2-isothiocarboxylic acids leads to radical coupling followed by cyclization. This cascade reaction gives thiazolo[5,4-d]thiazole derivatives as pure enantiomers. Under similar conditions, 2-methylbutyl esters of 2-isothiocyanatocarboxylic acids undergo intermolecular oxidative dimerization to give mixtures of thiazolo[5,4-d]thiazoles and 2,3-diisothiocyanatosuccinates. Application of the soft enolization technique to dimethyl α,α′-diisothiocyanatodicarboxylic esters gives novel cyclic 1,2-diisothiocyanato-1,2-dicarboxylates. Sodium enolates of 2-isothiocyanatocarboxylates, on the other hand, form 5-imino-2-thioxo-1,3-thiazolidine-4-carboxylic esters by nonoxidative dimerization. The mechanisms of the two reaction pathways are discussed.
Keywords: domino reactions; dimerizations; heterocycles; enols; titanium; diastereoselectivity